Pengaruh Peran Guru Akidah Akhlak sebagai Model dan Teladan Terhadap Kepribadian Siswa - Masiah, Masiah; Erdiansyah, Erdiansyah; Herawati, Herawati (Lembaga Sosial Rumah Indonesia, 2023)
The observation of an increase in students' moral values has been noted in several instances, indicating a pressing need for focused attention in this area. Islamic education has been identified as a potential avenue for the cultivation of a noble moral personality among students. This research aims to investigate the influence of the Akidah Akhlak teacher's role as a positive and negative model on students' personalities. The teacher's role as an independent variable (X1 and X2), and the students' personalities as the dependent variable (Y), with the population being ninth-grade students of MTs Negeri in Sekayu District. The F-test of X1, X2, and Y resulted in a Sig of 0.001 and F-count of 7.508. Meanwhile, the T-test revealed a Sig of 0.000 and 0.044 for X1 and X2, respectively. Based on the F and T-test results, it can be concluded that there is a positive and significant influence of the Akidah Akhlak teacher's role as a good model and example on students' personalities. Additionally, there is a positive and significant impact of the teacher's role as a negative model and example, albeit to a lesser extent, on students' personalities.